The Early Labor Market Impacts of COVID-19 in Developing Countries : Evidence from High-Frequency Phone Surveys - Khamis, Melanie; Prinz, Daniel; Newhouse, David; Palacios-Lopez, Amparo; Pape, Utz; Weber, Michael (World Bank, Washington, DC, 2021)
The economic crisis caused by the Coronavirus (COVID-19) pandemic sharply reduced mobility and economic activity, disrupting the lives of people around the globe. This brief presents estimates on the crisis’ impact on labor markets in thirty-nine countries based on high-frequency phone survey (HFPS) data collected between April and July 2020. Workers in these countries experienced severe labor market disruptions following the Coronavirus (COVID-19) outbreak. Thirty-four percent of respondents reported stopping work, twenty percent of wage workers reported lack of payment for work performed, nine percent reported job changes due to the pandemic, and sixty-two percent reported income loss in their household. Measures of work stoppage and income loss in the HFPS are generally consistent with gross domestic products (GDP) growth projections in Latin America and the Caribbean but not in Sub-Saharan Africa, indicating that the phone survey data contributes valuable new information about the impacts of the crisis. Ensuring availability of such critical data in the future will require investments into statistical and physical infrastructure as well as human capital to set up Emergency Observatories, which can rapidly deploy phone surveys to inform decision makers.